Gaucher’s disease - a review of the most important information about the disease in Paediatrics - Jarmołowicz, Jakub; Krzeszowska, Paulina; Kujawa, Aleksandra; Krochmal, Karolina; Samoraj, Adrianna; Zajączkowski, Jakub; Marrodán-Wojtczak, Karolina; Wilk, Jan; Stępniak, Kacper; Kuźma, Radosław (Quality in Sport, 2025)
Gaucher disease is an autosomal recessive spirochete disease caused by a deficiency of the enzyme glucocerebrosidase. A mutation in the GBA1 gene induces the accumulation of abnormal products in macrophages resulting in the transformation into Gaucher cells in many organs. There are three main types of the disease, 1 being the most common type (non-neuropathic). The 2nd and 3rd types of the disease are neuropathic types and these occur mainly in childhood. Among paediatric patients, Gaucher’s disease manifests mainly with enlargement of the liver, spleen, thrombocytopenia, anaemia, but skeletal, ocular and central nervous system symptoms may be present. Diagnosis based on enzymatic and genetic tests - analysis of the GBA1 gene mutation - is essential to prolong patients’ lives, improve their quality of life and select an appropriate form of treatment. Currently, care for patients with this disease is based on ERT (enzyme replacement therapy), SRT (substrate replacement therapy). The disease is characterised by rather non-specific symptoms and course, and can be interpreted by physicians as a haematological-proliferative disease due to frequent changes in the structure of the liver, spleen and changes in blood morphological parameters. Increased awareness among doctors of the symptoms of this disease would allow earlier detection and implementation of treatment. This paper presents the current diagnostic and therapeutic methods and the characteristic symptoms any paediatrician may encounter. The challenges of diagnosing this disease are also highlighted.